Toxicity study of the oil dispersant Corexit 9527 on Macrobrachium rosenbergii (de Man) egg hatchability by using a flow-through bioassay technique - Law, A.T. (Elsevier, 1995)
The effect of the oil-spill dispersant Corexit 9527 on egg-hatching rate of Macrobrachium rosenbergii (de Man) was studied by using an innovated flow-through bioassay technique. This bioassay method relies on the fact that M. rosenbergii fertilized eggs when detached from the mother prawn were able to hatch artificially. The flow-through system generated a stable and good water quality environment for hatching the eggs successfully. The Corexit 9527 had a pronounced effect on hatching rate of the M. rosenbergii eggs. In the control, the hatching rate of the eggs was 95·55% ± 1·74%. However, it was reduced drastically with increasing concentrations of Corexit 9527. A 100% inhibition of egg hatchability was found when the level of Corexit 9527 was higher than 250 mg litre-1. The EC50 and the EC95 values estimated by the probit method were 80·4 ± 5·5 mg litre-1 and 193·5 ± 39·9 mg litre-1 respectively (P = 0·05). The recommended safety level of Corexit 9527 for M. rosenbergii in Malaysian estuarine waters is below 40 mg litre-1.